Effects of dietary Chinese herbal mixtures on productive performance, egg quality, immune status, caecal and offspring meconial microbiota of Wenchang breeder hens - Liu, Mengjie; Huang, Jieyi; Ma, Ming; Huang, Gengxiong; Zhang, Yingwen; Ding, Yiqing; Qu, Qian; Lv, Weijie; Guo, Shining (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the effects of Chinese herbal mixtures (CHMs) on productive performance, egg quality, immune status, anti-apoptosis ability, caecal microbiota, and offspring meconial microbiota in hens. A total of 168 thirty-week-old Wenchang breeder hens were randomly divided into two groups, with each group comprising six replicate pens of fourteen hens. The groups were fed a basal diet (CON group) and a basal diet with 1000 mg/kg CHMs (CHMs group) for 10 weeks. Our results showed that dietary supplementation with CHMs increased the laying rate, average egg weight, hatch of fertile, and offspring chicks' weight while concurrently reducing the feed conversion ratio (FCR) and embryo mortality (p < 0.05). The addition of CHMs resulted in significant improvements in various egg quality parameters, including eggshell strength, albumen height, haugh unit, and the content of docosatetraenoic acid (C20:4n-6) in egg yolk (p < 0.05). The supplementation of CHMs had a greater concentration of IgA and IgG while decreasing the content of IL-6 in serum compared with the CON group (p < 0.05). Addition of CHMs to the diet increased the expression of Bcl-2 and IL-4 in liver and ovary, decreased the expression of IL-1β, Bax, and Caspase-8 in jejunum and ovary, and decreased the expression of NF-κB in liver, jejunum, and ovary (p < 0.05). Moreover, dietary CHMs reduced the abundance of Desulfovibrio in caecal microbiota as well as decreased the abundance of Staphylococcaceae_Staphylococcus and Pseudomonadaceae_Pseudomonas in the offspring meconial microbiota (p < 0.05). In conclusion, the CHMs could improve productive parameters by enhancing immune status, anti-apoptosis capacity, and modulating the caecal microbiota of Wenchang breeder hens, as well as maintaining the intestinal health of the offspring chicks.